2016
DOI: 10.1016/j.cgh.2016.05.041
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Age, Sex, Body Weight, and Quantity of Alcohol Consumption on Occurrence and Severity of Alcoholic Hepatitis

Abstract: Background & Aims Only a minority of heavy drinking individuals develop alcoholic hepatitis (AH), for unclear reasons. We analyzed data from the Translational Research and Evolving Alcoholic Hepatitis Treatment cohort: subjects who drink heavily with normal results from liver tests (controls) and patients with AH. We examined risk factors for the development of AH including body mass index (BMI), drinking pattern and quantity, and sex. Methods We compared data from 145 patients with AH cases and 124 controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 52 publications
(80 citation statements)
references
References 29 publications
(36 reference statements)
3
71
1
Order By: Relevance
“…Importantly, our data refutes previous assertions about possible precipitants of AH, in particular, that binge drinking precipitates the disease, and also that paracetamol use may cause it [10]. Other papers describe risk factors – for example, BMI [9, 11] – without addressing precipitants.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Importantly, our data refutes previous assertions about possible precipitants of AH, in particular, that binge drinking precipitates the disease, and also that paracetamol use may cause it [10]. Other papers describe risk factors – for example, BMI [9, 11] – without addressing precipitants.…”
Section: Discussioncontrasting
confidence: 54%
“…The TREAT consortium recently reported on characteristics of patients with AH and a control group of patients with ArLD [9]. Interestingly, patients with AH tended to drink less than the control group: approximately 10 standard drinks per day.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical characteristics of the patients recruited into the TREAT001 study have been previously reported (Liangpunsakul et al, 2016). The patients were mainly middle-aged white men who were very heavy drinkers.…”
Section: Eligibility For Clinical Trialsmentioning
confidence: 99%
“…Language barriers with Spanish-speaking patients also hinder recruitment. Hispanic patients may have an increased risk of AH (the PNLPA3 variant, common in Hispanics, which confers risk of non-alcoholic steatohepatitis (Romeo et al, 2008) and alcoholic cirrhosis (Stickel et al, 2011; Buch et al 2015) also increases risk for AH (Liangpunsakul, et al, 2016). Future studies could incorporate validated and IRB-approved Spanish translations of consent documents, surveys, and other data collection instruments (e.g., the Time Line Follow-Back survey, and instruments used to detect concomitant mental health disorders).…”
Section: Recommendations To Improve Recruitment and Retention In Traimentioning
confidence: 99%